Pengaruh Corporate Sustainability Reporting Terhadap Profitabilitas PerusahaanNon-Keuangan di Indonesia Pada Periode 2015 – 2019 - Deyas, Calista Eightten; Sidjabat, Mona Ridho (UI Scholars Hub, 2022)
This study aimed to examine the effect of corporate sustainability reporting on firm profitability and show differences in revenue, revenue growth, profitability, and change in total asset between High ESG Score and Low ESG Score firms in Indonesia. This study used a sample of 30 non-financial public firms during 2015 – 2019. This study also used balanced panel data and panel data regression, with the random effect model estimation techniques. The study found that corporate sustainability reporting didn’t significantly affect firms’ profitability. In addition, the study showed that there are no significant differences in revenue growth, profitability, and change in total asset between High ESG Score and Low ESG Score firms in Indonesia. However, revenue differences between High ESG Score and Low ESG Score firms in Indonesia were found in this study.